Study of Antioxidant Properties and the Significance of Testa in Irvingia Spp (Wombolu and Gabonensis) - Audu, Omale Jamila; Ele-Ojo, Ojogbane; Ilecholubo, Awodi Patience (Emerging Challenges in Agriculture and Food Science Vol. 3, 2022)
The physical properties and antioxidant activity of oil extracts from Irvingia gabonensis (Ig) and Irvingia wombolu (Iw) kernels were investigated. Both varieties do not bear fruit at the same time of year. Furthermore, the effect of testa on antioxidants was investigated. Total Phenolics (TP), Ferric Reducing Antioxidant Power (FRAP), Total Antioxidant Activity (TAA) by thiocyanate (-SCN) method, and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) techniques were used to measure antioxidant activity. Regardless of the time of investigation, both oil extracts exhibited high antioxidant activity ranging from 61 to 93 percent. Mean inhibitory concentration, IC50 of Irvingia spp was 15.4 µg/ml compared with those of reference Quercetin and Vitamin C recorded as 4.38 and 1.85 µg/ml respectively. The role of testa in preventing autoxidation was statistically significant (p<0.05). IC50 of Irvingia wombolu with testa, Iwt (4.86 µg/ml) was comparable to that of Quercetin. TAA using the –SCN method distinguished the best between samples with and without testa. The study concluded that the oil extract of Irvingia kernels contains a high level of phenolic substances capable of inhibiting lipid autoxidation and is suitable for use as a quality oil in animal and human diets. It is strongly suggested that intact kernels of Irvingia be used with testa.